Nanoparticle in Asphalt Binder: A State-of-The-Art Review - Putra Jaya, Ramadhansyah; K. A., Masri; Norhidayah, Abdul Hassan; Mohd Rosli, Hainin; Muhammad Naqiuddin, Mohd Warid; Haryati, Yaacob; M. K. I. M., Satar; Juraidah, A. (IOP Publishing, 2020)
Increasing traffic volumes and the rising cost of bitumen making it necessary to improve the performance of asphalt binder through bitumen modification. Various types of modifiers have been employed as bitumen binders in order to improve the bitumen mixture, particularly with regard to its resistance to aging, cracks due to fatigue and thermal conditions, moisture-induced damage and permanent deformation. This review study summarizes the performance of nanoparticles as an asphalt modifier. Several relevant literatures were reviewed, which related to the matter associated with nanomaterials such as nano-silica, carbon nano-tubes and nano-titanium dioxide. Recent studies showed that the utilisation of nanoparticle gave great benefits in many ways.For instance, nano kaolin as a mineral clay promises non-hazardous effects to road users. This can result in a healthy environment and help towards increasing the application of green technology road construction.